The internationalization process of higher education institutions(HEIS) and the roles and challenges of academic leaders - Mansor, Zuraina (2012)
Education now is commonly agreed has become a part of globalization package. This is because through internationalization of higher education, for example, a country shows how it responds to the impact of globalization. This is because nowadays, education stands as one important element to bring national income as well as investment for building human capital, who will become a driver for technological innovation and economic growth in the world-wide market. Thus it is suggested by improving the educational status of a society, the multi-faceted development of its people can be achieved and prolong. Thus, it is unavoidable for many countries to take part in the globalization and internationalization of their Higher Education Institutions (HEIs), and to ensure their education is facilitating the development of human capital needs and interest. This study has been conducted to focus on the management issues especially the academic leaders’ roles and responsibilities in facing the opportunities and challenges in internationalization of their institutions. Data were collected using primary and secondary sources. The findings would suggest the summary of some challenging roles of today and future academic leaders in managing the internationalization process as well as to sustain their institutions reputations as part of world-wide HEIS.